Enhancing Higher Education Sustainability Through Quality Management Models - Lubis, Andrew Satria; Zulfan,; Sinulingga, Samerdanta; Ismayadi, Ismayadi (Journal of Research in Mathematics Trends and Technology, 2024)
Higher education, as part of the service sector, faces significant challenges in managing its systems effectively. To remain competitive and foster growth, private universities require sustainable models that enhance their quality and operational efficiency. This research explores sustainability models for private universities by conducting field surveys and distributing online questionnaires. Data analysis was performed using descriptive statistics and Structural Equation Modeling (SEM). The descriptive analysis highlights key demographic and behavioral characteristics of the respondents, while SEM reveals relationships and factors influencing customer satisfaction and loyalty. Results show that planning, governance, and administration significantly impact education quality, which directly influences the sustainability of private universities. The study also finds that the roles of students, alumni, reputation, and cooperation are crucial in maintaining long-term institutional sustainability. These findings offer practical insights for improving education quality and formulating strategies for private universities to achieve sustainable development.